2016
DOI: 10.3390/en9080645
|View full text |Cite
|
Sign up to set email alerts
|

A Concentrator Photovoltaic System Based on a Combination of Prism-Compound Parabolic Concentrators

Abstract: Abstract:We present a cost-effective concentrating photovoltaic system composed of a prism and a compound parabolic concentrator (P-CPC). In this approach, the primary collector consists of a prism, a solid compound parabolic concentrator (CPC), and a slab waveguide. The prism, which is placed on the input aperture of CPC, directs the incoming sunlight beam to be parallel with the main axes of parabolic rims of CPC. Then, the sunlight is reflected at the parabolic rims and concentrated at the focal point of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 29 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…This type of solar cell is Because of the simplicity of the proposed flat CPV system in terms of its shape, weight, operating principle, and cost, it can easily be installed on rooftops. The adoption of flat CPVs for rooftop installation will address the apparent huge demand for commercialization [17]. The aim of the present research is to design a flat CPV system suitable for residential rooftops; therefore, a brief comparison between our proposed system and widely used PV panels is essential.…”
Section: Discussionmentioning
confidence: 99%
“…This type of solar cell is Because of the simplicity of the proposed flat CPV system in terms of its shape, weight, operating principle, and cost, it can easily be installed on rooftops. The adoption of flat CPVs for rooftop installation will address the apparent huge demand for commercialization [17]. The aim of the present research is to design a flat CPV system suitable for residential rooftops; therefore, a brief comparison between our proposed system and widely used PV panels is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Vu and Shin proposed a combination of a prism, a solid dielectric CPC, and slab waveguide to achieve a high concentration and uniform energy flux distribution on the surface of the PV cells. The function of the prism is to refract the light into the CPC while the slab waveguide guides the sunrays into the solar cells.…”
Section: Studies In the Literature On The Application Of Cpcs To Photmentioning
confidence: 99%
“…In their study, the analysis confirmed that the PV module with individual cells and the effect of non‐uniform illumination resulted in high‐power output. In addition, the use of CPC in two stage‐concentrating systems has been reported to create uniform flux distribution along the PV module …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the use of CPC in two stage-concentrating systems has been reported to create uniform flux distribution along the PV module. [48][49][50][51][52] Another way of mitigating non-uniform illumination in PV application is the use of planar concentrators, which illuminate the receiver uniformly. [53][54][55][56] Nevertheless, the application of planar concentrators in PVs is limited by their low-concentration ratios.…”
Section: Introductionmentioning
confidence: 99%